2010
DOI: 10.1002/adsc.200900793
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalysed Direct Arylation of Heteroaromatics Bearing Unprotected Hydroxyalkyl Functions using Aryl Bromides

Abstract: International audienceHeteroaromatics bearing unprotected hydroxyalkyl functions can be arylated using aryl or heteroaryl bromides, via palladium-catalysed carbon-hydrogen bond activation/arylation. Good yields were generally obtained using 0.01-0.5 mol% of the air-stable palladium acetate complex as the catalyst. The nature of the base was found to be crucial for the selectivity of this reaction. Potassium acetate led to the direct arylation products whereas caesium carbonate led to the formation of the ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 80 publications
2
36
0
Order By: Relevance
“…2,9-Dimethyl-1,10-phenanthroline (L 2 ) and 1,10-phenanthroline-5,6-dione (L 5 ) gave only traces of 2 ba, demonstrating that sterically hindered or electrondeficient ligands negatively affected the reaction (entries 8 and 11). palladium catalysts were screened and found to offer no improvement in the yield (entries [15][16][17][18][19][20]. Transition-metal-catalyzed CÀ C bond cleavage reactions of furfuryl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…2,9-Dimethyl-1,10-phenanthroline (L 2 ) and 1,10-phenanthroline-5,6-dione (L 5 ) gave only traces of 2 ba, demonstrating that sterically hindered or electrondeficient ligands negatively affected the reaction (entries 8 and 11). palladium catalysts were screened and found to offer no improvement in the yield (entries [15][16][17][18][19][20]. Transition-metal-catalyzed CÀ C bond cleavage reactions of furfuryl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the previously reported results using 2-thiophenemethanol. 18 It should be noted that the use of n-Bu 3 N as the base gave no coupling product (Table 7, entry 2). On the other hand, a better regioselectivity in favour of the arylation at C2 was observed in xylene, but only a partial conversion of 4-bromobenzonitrile was obtained (Table 7, entry 3).…”
Section: Methodsmentioning
confidence: 98%
“…18 The use of such substrate bearing an unprotected functions would be very useful in organic synthesis since it would allow to avoid the protection/deprotection sequence, and therefore should provide a more environmentally and economically attractive access to such arylated heteroaromatics. Moreover, the presence of such functional group on thiophene might have an influence on the regioselectivity of the arylation due to a possible coordination of the hydroxy group to palladium.…”
Section: Methodsmentioning
confidence: 99%
“…However, with strong deactivated aryl bromides, such as 4-bromoanisole and 4-bromo-N,NdimethylA C H T U N G T R E N N U N G aniline (entries 61 and 62, Table 2) no coupling product was obtained also using 0.5 mol% Pd- 2 as the catalyst precursor. [86] Doucet also found that, although compound 13l underwent C-5 arylation with electron-deficient and electron-neutral aryl bromides in moderate to good yields using 0.1 mol% Pd- 2 as the catalyst precursor and KOAc as the base, [86] the use of 1 mol%…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
“…of 2-bromobenzonitrile and 3-bromotoluene utilizing controlled microwave heating (entries 2 and 3, respectively, Table 2). Moreover, a low catalyst loading of only 0.01-00.5 mol% was used by Doucet and co-workers for the PdA C H T U N G T R E N N U N G (OAc) 2 -catalyzed reaction between a variety of (hetero)aryl bromides and thiophen-2-ylmethanol (13i) (entries 59, 60 and 63-65, Table 2), [86] 1-(thiophen-2-ylethanol (13j) (entries 66 and 67), [86] N-(thiophen-2-ylmethyl)acetamide (13k) (entries 68-74, Table 2) [22] and N-[2-(thiophen-2-yl)ethyl]acetamA C H T U N G T R E N N U N G ide (13l) (entries 75-78, Table 2) [22] under ligandless conditions. Notably, the reaction conditions of entries 59, 60 and 63-65 of Table 2 proved also to be suitable for the high yielding C-5 arylation of 13i with electron-deficient aryl bromides such as 2-bromobenzonitrile and 1-bromo-3,5-bis(trifluoromethyl)benzene.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%